Economic transition in Yugoslavia: A view from outside - Simon Đerđ mlađi (Međunarodni Problemi)
Yugoslavia, once an advanced country in market reforms, was one of the least transformed countries in Eastern Europe in the nineties. Such a situation was caused by the civil war, policy of the Milošević’s regime and international sanctions. The resistance of the ruling conservative forces made it impossible to establish an adequate reform policy. Thus, the transition stopped short halfway. The situation has radically changed only since the autumn of 2000, after Milošević’s downfall, when after the gradual lifting of international isolation, economic and political reforms were given a new stimulus, and the country could start the process of European integration. This article is an attempt to give an overview of the transition of the Yugoslav economy in the last ten years or so. The growth rate of Yugoslavia’s GDP is compared not only with that of its neighbouring countries, i.e. other former socialist countries of South-Eastern Europe (Albania, Bosnia and Herzegovina, Bulgaria, Macedonia, and Romania) but also with that of other transition economies in Central and Eastern Europe, including the Commonwealth of Independent States. A particular attention is given to the role of research and development (R&D) in Yugoslavia in the nineties as compared to Croatia, Slovenia, and the United States. The structural changes in the Yugoslav economy during the past decade are analysed together with property relations as well as the issues concerning small and medium-sized enterprises (SMEs). At the sectoral level, it is the performance of manufacturing and agriculture that is separately explored. In relation to this, wage formation and relative wage levels in Yugoslavia’s manufacturing are viewed regarding the country’s international competitiveness and wider characteristics of globalising world economy. In analysing the role of external sources in the Yugoslav economy, the problems of foreign trade, external indebtedness, and attraction of foreign direct investment (FDI) are emphasized together with the economic assistance rendered to the FRY by the European Union. Regarding the important indicator of openness, i.e. the share of exports and imports in GDP, a comparison is made between Yugoslavia, on one hand, and Croatia, Slovenia, the European Union, and the United States, on the other. The economic policy of Milošević’s regime is contrasted with that of the new democratic government that came to power after the events in October 2000. Stabilisation, liberalisation, privatisation, and institutional reform are considered giving particular attention to the experience of the member republics of the Yugoslav federation: Serbia and Montenegro. The author comes to the following conclusions: in transition countries stabilisation, liberalisation, and privatisation cannot be successful without carrying out a comprehensive, deep reform of the system of political institutions that along with creation of conditions for establishment of democracy and its strengthening also enables building of a modern and efficient market economy. This complicated and often contradictory process could come across serious obstacles if the old state and party nomenclature in power retains the command economy without planning, and under demagogical, nationalistic, and populist slogans gets involved in wars even taking the risks of being put under international isolation. However, such an outdated economic system characterised by autarchy can only temporarily exist and hinder the unravelling of market reforms in the epoch of globalisation.